Inclusion of wheat bran in barley-soybean meal diets with different phosphorus levels for growing-finishing pigs II. Performance and bone mineralization in growing-finishing pigs - Helander, Eija; Partanen, Kirsi (Agricultural Research Centre of Finland, 1994)
Kasvatuskokeessa 144 lihasialla selvitettiin, parantaako vehnäleseen fytaasi ohrasta ja soijasta peräisin olevan fosforin hyväksikäyttöä ja voidaanko sillä näin ollen osittain tai kokonaan korvata rehuun normaalisti lisättävä epäorgaaninen fostori. Koe suoritettiin 2x3 faktorikokeena, faktoreina vehnäleseen määrä (0 tai 100 g/kg) ja fosforitaso (korkea, keskinkertainen ja matala). Keskinkertainen fosforitaso osoittautui riittäväksi sioille koko kasvatuskaudeksi (30-100 kg), mutta siat, jotka söivät koko kasvatuskauden ajan rehua, jonka fosforitaso oli matala, kasvoivat heikommin ja kuluttivat enemmän rehua kasvukiloa kohti kuin muut siat. Kuitenkin nämä siat kasvoivat loppukasvatusvaiheen aikana yhtä hyvin kuin muutkin siat. Tämä viittaa siihen, että loppukasvatusrehun fosforipitoisuutta voidaan alentaa nykyisestä tasosta. Vehnälese ei vaikuttanut sikojen kasvuun, rehunhyväksikäyttöön tai teuraslaatuun. Tulosten perusteella vehnälesettä voidaan lisätä sikojen kasvatusrehuun 1 00 g/kg tuotantotuloksia heikentämättä. Vaikka vehnäleseen fytaasi hieman paransikin matalafosforisella ruokinnalla olleiden sikojen sääriluun murtolujuutta, ei vehnälesettä kuitenkaan fosforin hyväksikäytön tehostamismielessä kannata rehuun lisätä.

The experiment was conducted to study whether wheat bran (WB) phytase could improve the availability of intrinsic phosphorus (P) in commercial barley-soybean meal diets enough to replace the added inorganic P partly or completely in the diets of growing-finishing pigs (30-100 kg). Performance as well as certain Chemical and physical parameters of the tibia and fibula bones were used as criteria for the WB phytase effect. The experiment was conducted using a 2x3 factorial arrangement. The factors were wheat bran (WB) level - either 0 (WB-) or 100 g/kg (WB+), and phosphorus level - high (HP), medium (MP) and low (LP) corresponding to 4.33 g, 2.99 g and 1.64 digestible P per a feed unit (FU = 0.7 kg starch equivalent), respectively. The measured digestible P contents of the diets were 4.2, 4.2, 2.7, 2.5, 1.4 and 1.8 g/kg DM, respectively. A content of 2.5-2.7 g of digestible P/kg DM in the diet proved to he sufficient for the whole growing period, but the lowest phosphorus levels led to an impaired growth rate., feed consumption and feed conversion ratio. However, after reaching 60 kg live weight, the pigs on LPWB- and LPWB+ diets were able to grow and utilize feed as effectively as the other pigs. WB at a level of 100 g/kg had no significant effect on the performance, feed conversion ratio or carcass quality criteria of the pigs on any diet. WB phytase showed a positive effect on bone breaking strength on the LP diet.
Keywords: Ko; lihasika; ruokinta; fosfori; phytin; phytase; growth; swine